IDENTIFYING DEIXIS IN THE SONG “HOW FAR I’LL GO” FROM MOANA MOVIE BASED ON THE PERSPECTIVE OF DISCOURSE ANALYSIS - Desi Peronika Purba; Nopa Marbun; Ima Betaria Silalahi; Mely Christi Sihotang; Herman Herman (Jurnal Scientia, 2023)
The goal of this research is to identify the use of deixis in a song in the perspective of discourse analysis. Descriptive qualitative research was implemented in this research. The data used in this research was the song entitled ‘How Far I’ll Go” which was the anthem song of Moana movie. The results of the research were personal, spatial and temporal deixis depicted in the song. There were 12 personal deixis, 5 spatial deixis, and 4 temporal deixis. As a conclusion, the personal deixis was the most dominant used in the song